2021
DOI: 10.1016/j.dsx.2020.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Managing Type 1 Diabetes among Saudi adults on insulin pump therapy during the COVID-19 lockdown

Abstract: Background and aims The coronavirus disease 2019 (COVID-19) pandemic has affected people's lives including patients with Type 1 diabetes mellitus (T1DM). We aimed to investigate the impact of the COVID-19 lockdown on psychological status, self-management behaviors, and diabetes care maintenance among Saudi adults with T1DM using insulin pump therapy. Methods This cross-sectional study used a web survey to collect data on Saudi adults with T1DM who were treated in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 23 publications
(21 reference statements)
5
27
0
Order By: Relevance
“…Additionally, our participants obtained an average perception value of 67.76 ± 19.9%, suggesting that the majority had a good perception toward the virtual phone clinic for the routine care of T1DM. This is in agreement with another cross-sectional web-based study done in our institution during lockdown in Saudi Arabia, wherein the majority of insulin pump-treated T1DM patients rated the virtual phone visit they had as beneficial [ 18 ]. Moreover, Fung et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, our participants obtained an average perception value of 67.76 ± 19.9%, suggesting that the majority had a good perception toward the virtual phone clinic for the routine care of T1DM. This is in agreement with another cross-sectional web-based study done in our institution during lockdown in Saudi Arabia, wherein the majority of insulin pump-treated T1DM patients rated the virtual phone visit they had as beneficial [ 18 ]. Moreover, Fung et al.…”
Section: Discussionsupporting
confidence: 90%
“…With regards to patient perception toward the virtual phone clinic in the present study, around two thirds of patients agreed or strongly agreed that virtual phone clinics have improved their diabetes control, ability to routinely conduct their follow-up with their physician, and improved their access to healthcare, as well as feeling satisfied with the phone call-assisted healthcare service compared to traditional clinics. Telemedicine has been reported to allow patients with diabetes to easily communicate with a healthcare provider in the comfort of their home [ 9 , 18 ], and patients were able to receive their healthcare needs [ 18 ]. The online survey study of Fung et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the quality assessment, 8 studies (32%) were found to be unsatisfactory [16,[19][20][21][22][23][24][25] and 17 (68%) studies met the criteria of satisfactory quality using NOS quality assessment criteria. The major sources of bias were representativeness (n = 24), control of potential confounders (n = 24), and unpowered sample size (n = 21).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…The data was collected by phone call interviews using a well-structured questionnaire. Most of it was taken from Sultan F. Magliah and his colleague's questionnaire in Saudi Arabia (10).…”
Section: Data Collectionmentioning
confidence: 99%